Secret crush - Carrol, Jacqueline (New York : HarperCollins, 2002)
Chloe and Riley Carlson have so much to do and so little time. This time they have to set up a date between two of their friends, learn how to use power tools, show the conceited boy who's boss and hang out with their secret crush.
"A Parachute Press book".
"Based on the hit TV series"--Cover.
"Based on the teleplay by Michael Baser and Frank Dungan".
"HarperEntertainment".
All Ages.
Keywords: Dating (Social cusoms) -- Juvenile fiction; Series, Juvenile